(3GdJbjjO deYQag QhGI GdSff hGdCSGfjOs - (3GHf ofbWI GdMfHdj GdHZOGOj , eMeO Hf YHO GdZfj Hf CHj HcQ Hf TLGY, eYjf GdOjf, GHf ofbWI , CHh HcQ J (B629 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO NGJe GdfHjjf s
(3BNQgG (B:s
(3BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3fSNI cJHJ HNW ZjQ eYLe ai GdZGdHs
(3hYdjgG hbbjI eDQNI HSfI (B755 (3hajgG jSei GdcJGH HGdhajGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B179s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B97 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs